Malondialdehyde and Total Antioxidant Levels and Hematological Parameters of Beef Cattle with Coccidiosis - Yılmaz, Seval; Issı, Mustafa; Kandemır, Fatih Mehmet; Gul, Yusuf (Van Yüzüncü Yıl Üniversitesi, 2014)
The present study evaluates the malondialdehyde (MDA) level of serum lipid peroxidation and total antioxidant capacity in order to determine the effects of coccidiosis on oxidative stress in beef cattle. It will be determined in this study whether lipid peroxidation plays a role in the pathogenesis of the disease. This study included 10 beef cattle diagnosed with coccidiosis via clinical and stool examinations (Patient group) and 10 healthy matched animals from the same barn (Control group). General clinical findings (body temperature, heart and respiration rates, and rumen movements), hematological parameters (total leukocyte count, erythrocyte count, hematocrit value and hemoglobin count), and serum MDA levels and total antioxidant capacities were determined.  A significant increase was observed in the body temperature, heart and respiration rates, total leukocyte count, and serum MDA levels of the patient group compared to the controls, while the rumen movements, hematocrit and hemoglobin values, and serum total antioxidant capacities showed significant reductions (P<0.05). The results of the present research suggest that prophylactic measures should be taken in animals with coccidiosis, as the defense system might be infected due to the increase in MDA level. It will be shown whether these parameters can be taken as references with other parameters in order to make diagnosis as well as the efficiency of treatment.

Bu çalışmada, koksidiyozisin oksidatif stres üzerine etkilerini araştırmak için serum lipid peroksidasyon ürünü olan malondialdehid (MDA) düzeyi ile total antioksidan kapasitesinin değerlendirilmesi ve lipid peroksidasyonun hastalığın patojenezinde etkisinin araştırılması amaçlanmıştır. Klinik ve dışkı muayenesinde koksidiyozis teşhisi konan 10 hayvan (hasta grubu) ile birlikte aynı ahırda sağlıklı oldukları belirlenen benzer özellikteki 10 hayvandan (kontrol grubu) oluşan toplam 20 baş besi danası araştırma materyalini oluşturmuştur. Tüm hayvanların genel klinik muayene bulguları (vücut sıcaklığı, kalp ve solunum frekansı ile rumen hareketleri) ve hematolojik parametreleri (total lökosit sayısı, eritrosit sayısı, hematokrit değer ve hemoglobin miktarı) ile serum MDA düzeyleri ve total antioksidan kapasiteleri belirlenmiştir.  Hasta grubunda vücut sıcaklığı, kalp frekansı, solunum frekansı, total lökosit sayısı ve serum MDA düzeylerinin istatistiksel olarak önemli derecede arttığı, rumen hareketi, hematokrit ve hemoglobin değeri ile serum total antioksidan kapasitesinin düştüğü görülmüştür (P<0.05). Sonuç olarak, MDA düzeyinin artmasına bağlı olarak savunma sisteminde bozulma olabileceğinden koksidiyozisli hayvanlarda profilaktik tedbirlerin alınmasının gerekli olduğu kanaatine varılmıştır. Bu parametrelerin tedaviyi etkin hale getirmenin yanı sıra tanı koymak için diğer parametreler ile birlikte referans olarak alınabileceğini gösterebilir.
Koksidiyozisli Besi Danalarında Malondialdehid ve Total Antioksidan Düzeyleri ile Hematolojik Parametreler